The Discourse of TV Arabic Advertisement With Reference to English - Dr. Nashwan Mustafa Al-Sa ati (PROSPECTIVE RESEARCHES, 2023)
This study investigates the discoursal structure of TV commercial (consumer) advertisements in Arabic. It focuses on analyzing and describing the visual and linguistic verbal strategies and their structures, specifically aspects attempting to persuade the viewers together with their syntactic and semantic features, which are reached through tape-recorded situations of 75 samples shown on two channels of Nile satellite. However, non- verbal strategies are going to be tackled just in passing. It is believed that an effective advertisement can be best presented if the advertiser is well acquainted with the linguistic and rhetorical devices used in the advertising message. In addition, since both Arabic and English have increasingly come world-wide use, we hope this research raise the level of awareness of the persuasive techniques used in advertisements. Such awareness might be important, for example, for students of translation whom we hope to enable to a better use of Arabic and English through exposure to the use of this particular variety of language. We hypothesize that TV commercial advertisements vary in the strategies adopted in presenting the advertising message. We also hypothesize that exaggeration is the most prominent strategy. The study has come up with the findings that first, TV commercial advertisements involve various strategies accompanied by some modes that help for an effective presentation of the message. Second, the study proves that TV commercial advertisements are highly exaggerated; this is really reflected in the use of adjectives that are mostly superlative.